ANALISIS PENERAPAN SAK EMKM DALAM PENYUSUNAN LAPORAN KEUANGAN PADA USAHA MIKRO KECIL MENENGAH DI KOTA BATAM - Melinda, Melinda A. J Munthe; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2023)
This study aims to analyze the application of SAK EMKM in the preparation of financial reports on small and medium micro businesses in Batam City. This study used a descriptive and quantitative statistical approach with a population of 700 MSMEs registered with the Batam City Cooperatives and Small and Medium Enterprises Office and the sample in this study consisted of 100 respondents and used a questionnaire as a data collection instrument. From the data analysis, it was found that SAK EMKM did not affect financial reports with t count (1.276) < t table (1.983) and MSME socialization had an effect on financial reports with t count (6.462) > t table (1.983). Simultaneously the results of the EMKM SAK F test and MSME outreach have an effect on financial reports with a calculated F value (28.566) > F table 2.69)